Characteristics and Influencing Factors of Healthcare Utilization in Post-conflict Primary Care Attendees in Northern Sri Lanka - Doherty, Shannon; Sureshkumar, Diliniya Stanislaus; Thayakaran, Rasiah; Surenthirakumaran, Rajendra (Frontiers in Health Services, 2022)
Sri Lanka’s healthcare systems attempts to provides access to universal healthcare services for all citizens and is designed to be free of out-of-pocket payments. Despite a 30-year civil conflict, natural disasters, and COVID-19, the healthcare system within the country remains robust and strong. However, due to a lack of formalized pathways and centralized record keeping, the pattern of service utilization is still relatively unknown, which raises concerns regarding effective allocation of scarce resources and efficiency of referral pathways. To address this gap in knowledge, part of the parent study (COMGAP-S), consisted of a survey on healthcare service use conducted among adults attending primary care facilities. The results from this quantitative data analysis indicate the majority of people seeking care originate from rural areas, are older (50+), attend divisional hospitals, and report paying fees at point of contact. Our findings indicate a need for more efficient use of healthcare services, creation of referral routes to ensure limited healthcare resources are used effectively. Additionally, further investment in services is needed to ensure Sri Lanka’s healthcare system meets the standard of universal healthcare as proposed by the World Health Organisation. These findings address a gap in knowledge for national decision-makers within Sri Lanka along with other similar post-conflict healthcare settings across the globe.